Effects of a Vibro-Tactile P300 Based Brain-Computer Interface on the Coma Recovery Scale-Revised in Patients With Disorders of Consciousness - Murovec, Nensi; Heilinger, Alexander; Xu, Ren; Ortner, Rupert; Spataro, Rossella; La Bella, Vincenzo; Miao, Yangyang; Jin, Jing; Chatelle, Camille; Laureys, Steven; Allison, Brendan Z.; Guger, Christoph (Frontiers in Neuroscience, 2020)
Persons diagnosed with disorders of consciousness (DOC) typically suffer from motor and cognitive disabilities. Recent research has shown that non-invasive brain-computer interface (BCI) technology could help assess these patients’ cognitive functions and command following abilities. Twenty DOC patients participated in the study and performed 10 vibro-tactile P300 BCI sessions over 10 days with 10 runs each day. Changes of the BCI classification accuracy were investigated over the 10 days. Beside that the CRS-R score was measured before and after the 10 vibro-tactile P300 sessions. In the first run 10 patients had a classification accuracy above chance level (>23 %). In the best run every patient reached an accuracy ≥ 60 %. The grand average accuracy in the first session for all patients was 40 %, in the best session the grand average accuracy was 88 % and the median accuracy of all sessions was 21 %. The CRS-R scores compared before and after 10 VT3 sessions for all 20 patients are showing significant improvement (p = 0.024). Twelve of the twenty patients showed an improvement of 1 to 7 points in the CRS-R score after the VT3 BCI sessions (mean: 2.6). 6 patients did not show a change of the CRS-R and 2 patients showed a decline in the score by 1 point. Of importance is that during the 10 sessions every patient achieved at least once an accuracy ≥ 60 % which tested successfully command following. This shows the importance of repeated measures when DOC patients are assessed. The improvement of the CRS-R score after the 10 VT3 sessions is an important fact for future experiments to test the training abilities with a larger group of the vibro-tactile BCI setup.